SEPULUH PERINTAH TUHAN BAGIAN KEDUA: KASIH TERHADAP MANUSIA DALAM TINJAUAN ETIKA KRISTEN - Christie Kusnandar (Jurnal Ilmiah METHONOMI, 2017)
In Christianity that is the foundation and source of ethical understanding are the Ten Commandments recorded in Exodus 20: 3-17. The contents of the Ten Commandments are the commands and prohibitions which must be obeyed by the Israelites in the Old Testament and the Christians in the New Testament today. Thus, The Ten Commandments is always relevant from time to time, as well as a moral basis, especially in an ethical lifestyle of Christians. However, in the practice application of The Ten Commandments, there is much understanding excessively, which shifted the real meaning. Therefore, it is necessary to have a proper understanding of the Ten Commandments in The Christian Ethics review, in order to produce relevance and implementation which accordance with the theological significance therein.